RETRACTED: Smart high-yield tomato cultivation: precision irrigation system using the Internet of Things - Singh, Debabrata; Biswal, Anil Kumar; Samanta, Debabrata; Singh, Vijendra; Kadry, Seifedine; Khan, Awais; Nam, Yunyoung (Frontiers in Plant Science, 2023)
IoT-based Smart Farming promises ultrafast speeds and near-real time response. Precision farming enabled by the Internet of Things has the potential to boost efficiency and output while reducing water use. Therefore, IoT devices can aid farmers in keeping tracks on crop health and development while also automating a variety of tasks (such as moisture level prediction, irrigation system, crop development, and nutrient levels). The IoT-based autonomous irrigation technique makes exact use of farmer's time, money, and power. High crop yields can be achieved through consistent monitoring and sensing of crops utilising a variety of Internet of Things (IoT) sensors to inform farmers of optimal harvest times. In this paper, a smart framework for growing tomatoes is developed, with influence from Internet of Things (IoT) devices or modules. With the help of Internet of Things (IoT) modules, we can forecast soil moisture levels and fine-tune the watering schedule. To further aid farmers, a smartphone app is currently in development that will provide them with crucial data on the health of their tomato crops. Largescale experiments validate the proposed model's ability to intelligently monitor the irrigation system, which contributes to higher tomato yields.